The Effect of Peritubal Infiltration with Bupivacaine and Morphine on Postoperative Analgesia in Patients Undergoing Percutaneous Nephrolithotomy - Isra Karaduman; Derya Karasu; Canan Yilmaz; Sedat Oner; Hilal Erdem Solak; Gulsen Korfali (Pain Research and Management)
Objective. We aimed to investigate the effect of peritubal local anesthetic and opioid infiltration on pain scores and analgesic consumption in patients who underwent percutaneous nephrolithotomy. Material and Methods. Patients aged between 18 and 65 years and ASA I-III were included in this double-blind, randomized study. The patients were divided into two groups. All patients underwent spinoepidural anesthesia. 20 mL of 0.25 percent bupivacaine + 5 mg morphine (0.5 mL), in Group P (n=66), infiltrated the renal capsule, perinephric fat, muscles, subcutaneous tissue, and skin under fluoroscopy. In Group C (n=64), none of the patients received a peritubal injection. In the first 24 h pain scores, time of the first analgesic demand, the mean number of analgesic demands, and postoperative complications were compared between groups. Results. The mean VAS score at postoperative 8, 12, and 24 h and dynamic VAS score at postoperative 4, 8, 12, and 24 h were significantly lower in Group P. VAS score at postoperative 4 h was not significant. Time of the first analgesic demand was significantly longer in Group P. Conclusion. Our study results suggest that peritubal infiltration of bupivacaine with morphine after percutaneous nephrolithotomy is an effective method for postoperative pain control and reduces analgesic consumption.